Testbed Federation: An Approach for Experimentation-driven Research in Cognitive Radios and Cognitive Networking - DA SILVA, LUIZ (My University, 2011)
The sub-optimal exploitation of radio spectrum is widely accepted. Cognitive radio is a technol ogy that aims to address this issue and improve the overall efficiency of radio spectrum utiliza tion. However, this promising technology is far from being mature at present. In addition to the oretical research, experimentally-driven research is needed to convince industry and regulators of the benefits of cognitive radio. Several initiatives in this direction are taking place or are currently operational in both Europe and the United States. Most of them feature testbeds devoted to a specific radio access technology, network topology or application. A ?federation? of testbeds , addressing different applications or technologies each, can offer a richer and more powerful framework to tackle the large variety of challenges of experimentally- driven research in cognitive radio. The approach proposed in this paper combines th e existing capabilities of several testbeds to build a ?federation?. Th rough intelligent co mbination of hardware and software components originating from different te stbeds and linking them together via standardized interfaces, new components with enhanced capabilities are created. Another key feature of the ?federation? is the establishment of a benchmarking framework, enabling repeatable and reproducible results in a controlled wireless environment and allowing a fair comparison between experiments
Future Network and Mobile Summit
PUBLISHED
Keywords: Cognitive Radio; Cognitive Networking; Experimental Research; Software Defined Radio; Testbed; Federation; Interfaces; Benchmarking